Aitmad Ki Raftar - Covey, Stephen M. R.; Translated by Ibn-e-Saeed (Lahore Kitab Sarae, 2011)
The son of the author of the famed "7 Habits" books launches a new series on the defining principle of personal and economic success for the 21st century
Include Tables And Charts
Keywords: Aitbar Ka Asool -- Aitbaar Par Garift Hasil Karna -- Galtiyon Se Sikhna